Chemical profile and cellular antioxidant activity of artichoke by-products. Issue 12 (3rd November 2016) - Pagano, Imma; Piccinelli, Anna Lisa; Celano, Rita; Campone, Luca; Gazzerro, Patrizia; De Falco, Enrica; Rastrelli, Luca
Abstract : Artichoke byproducts, particularly bracts, are a promising and cheap source of inulin and caffeoylquinic acids for the production of food additives and nutraceuticals. Abstract : Artichoke by-products, produced from agricultural procedures and the processing industry, represent a huge amount of discarded material. In this research, the main artichoke by-products, bracts and leaves, were characterized in terms of their bioactive constituents (phenolic compounds and inulin) and cellular antioxidant potential to estimate their nutraceutical potential. The ultrahigh-performance-ultraviolet detection-high resolution mass spectroscopy (UHPLC-UV-HRMS) profiles of both by-products show that 5-caffeoylquinic acid and 1, 5-dicaffeoylquinic acid are the most abundant bioactive compounds, and the content of flavone glycosides can be used to discriminate between bracts and leaves. Artichoke by-products contain a remarkable overall phenolic content (0.5–1.7 g per 100 g dry matter), whereas they differ widely in the amounts of inulin with higher levels in bracts (3.8–8.2 g per 100 g dry matter). The cellular antioxidant activities of bract and leaf extracts (half maximal effective concentration (EC50 ) = 26.6–124.1 mg L −1 ) are better than or similar to that of a commercial leaf extract, and are related to the dicaffeoylquinic acid levels, particularly to 1, 5-dicaffeoylquinic acid. These results reveal that artichoke by-products are a promising and cheap source of bioactive compounds. Bracts could be used as a source of inulin and caffeoylquinic acids for the production of food additives and nutraceuticals and also as an alternative to the traditional application of leaf extracts.